PERLINDUNGAN KONSUMEN DALAM TRANSAKSI ELEKTRONIK - Andi Muhammad Rusdi (Fakultas Hukum Universitas Borobudur, 2023)
Electronic transactions are legal acts carried out using computers, computer networks and/or other electronic media. Now many consumers experience losses due to electronic transactions, such as goods sent to consumers that are damaged or do not match the photos of the goods on the internet. Therefore, this research will discuss forms of consumer rights violations in electronic transactions and legal protection for consumers in electronic transactions. This research is normative juridical research using secondary data. The results of the research are forms of consumer rights violations in electronic transactions, such as goods received in damaged condition, delays in delivery of goods by business actors, goods not matching what consumers ordered, and disinformation about goods in their actual condition in the Cash On Delivery (COD) system. So far, handling of consumer protection has not been carried out in an integrated manner, so that consumers' interest in their rights and obligations is still not as expected. Therefore, efforts need to be made to empower consumers, namely through integrated and comprehensive handling of consumer protection issues. Even though its birth is felt to be very late, it is already a step towards progress in the government's political will to further empower consumers and be able to respond to the importance of the existence of the rule of law.